Responsible sourcing for energy transitions: Discussing academic narratives of responsible sourcing through the lens of natural resources justice - Kügerl, Marie-Theres; Hitch, Michael; Gugerell, Katharina (Elsevier BV, 2023)
The Paris Agreement and the United Nations’ Sustainable Development Goals clearly demonstrate the need for global energy transitions. Evolving energy generation and the expansion of the renewable energy capacity and associated infrastructure contribute to changing and increasing demands for minerals and metals. The potential negative environmental, social and economic impacts of increased mineral resource production have been contested and are under increasing scrutiny by both academia and civil society. Responsible Sourcing (RS) has become a management approach for companies and policymakers to identify, monitor and address potential negative impacts along their raw materials’ supply chains. Although RS might contribute to sustainability along the supply chain, this paper raises the question of whether it also contributes to Natural Resource Justice (NRJ) in energy transitions. Based on a bibliometric network analysis, this study investigated current narratives of RS literature and to what degree core aspects of NRJ (e.g., distribution of benefits and burdens, power asymmetries, property rights) are reflected in the RS debate following a deductive approach. The results obtained show that compared with other sectors (e.g., timber, food, biomass, textiles) debates on RS in renewable energy-related sectors are still scarce and fragmented. The analysis indicates that different foci are aligned with one or more of the traditional three sustainability dimensions (i.e., environmental, social, economic), while few addressed aspects of NRJ. The authors observed a distinct lack of holistic justice considerations in the current RS debate and only a few individual issues are discussed, such as the detection of burden shifting, accountability for supplier behavior, and sharing of financial benefits. This research contributes to the understanding of different RS approaches and extends the RS discussion to NRJ considerations in energy transitions. It also points out important paths for future research to contribute to just energy transitions.